YOUNG-ONSET DIABETES MELLITUS: A DIAGNOSTIC AND MANAGEMENT DILEMMA - Murthy, Tilagamaty; Shudim, Saiful Shahrizal; See, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Type 1 diabetes mellitus is typically characterized by severe insulin deficiency with diabetes-related autoantibodies, though up to 5% of patients may have insulin deficiency without these autoantibodies. Diagnosing and managing diabetes in young adolescents can be particularly challenging. We present a case of a 12-year-old male diagnosed with diabetes after presenting with diabetic ketoacidosis (DKA), facing significant management challenges. CASE A 12-year-old male presented with severe DKA requiring ventilatory support in December 2021. His parents had no history of diabetes, but two older siblings had type 2 diabetes. After successful DKA management, he was discharged with basal-bolus insulin therapy. His HbA1c was 15%, and investigations revealed absent autoantibodies and a low C-peptide level (<3.33 pmol/L), suggesting insulin deficiency. Despite treatment, he experienced frequent nocturnal and postprandial hypoglycaemic episodes, as confirmed by continuous glucose monitoring (CGM). Reducing insulin doses did not resolve the hypoglycaemia. His condition was further complicated by non-compliance due to peer pressure and reluctance to take insulin while attending boarding school. A trial of basal insulin combined with sulfonylurea and close glucose monitoring resulted in over six months of stable glucose levels without hypoglycaemia. However, after a subsequent hospitalization for Klebsiella bacteraemia and uncontrolled glucose, basal-bolus therapy was reinstated in October 2024. During this hospitalization, C-peptide levels increased to 287 pmol/L. Given his ongoing difficulties with insulin compliance, a new trial with basal insulin and a DPP-IV inhibitor was initiated. CONCLUSION The initial diagnosis of Type 1B diabetes was suggested by low C-peptide and negative autoantibodies. Persistent hypoglycaemia despite low insulin doses and the challenge of non-compliance led to consideration of MODY variants, prompting trials with oral glucose-lowering drugs. Further genetic studies are needed for a definitive diagnosis.